SOCIAL SUPPORT IN INCREASING THE CONFIDENCE OF CHILD CLIENTS THROUGH PERSONALITY GUIDANCE IN BAPAS CLASS II PURWOKERTO - Triasih, Veronica Endah; Priyatmono, Budi (Universitas Nusa Cendana, 2025)
Criminal offenses committed by children can result in feelings of guilt, so that children tend to withdraw from the environment. This condition leads to a decrease in self-confidence in children. Low self-confidence in children can be improved through the provision of social support. Bapas, in this case, plays an important role in guiding juvenile clients with a restorative justice approach and cooperating with Pokmas Lipas in providing social support to juvenile clients. This study aims to answer the form of social support in increasing the confidence of juvenile clients and the obstacles faced in providing social support at LKSA Ar-Rohman. The data sources taken are primary data and secondary data. This research uses a qualitative method with a case study research design. Data collection through interviews, observation, and documentation. The data validity check used is the data triangulation technique. The results of the study are that the social support provided can increase the confidence of child clients and the obstacles faced in providing social support in the form of non-openness of child clients and limited human resources who provide social support to child clients at LKSA Ar-Rohman. Keywords: Social Support; Self-Confidence; Child Clients